Carolina courage - Ross, Dana Fuller (Canaan, NY Book Creations Inc. New York Bantam Books, 1991)
The saga of the Holt family continues with Janessa and Charley, who are both in Cherokee country using their knowledge of medicine to battle the disease that has stricken the Indians, and who end up fighting for their own lives
94531
Keywords: Family -- Fiction; North Carolina -- Fiction; Historical fiction